Respuesta :
Answer:
[tex]a_{1} = 6, a_{n} = 6 + a_{n - 1}, n > 0[/tex]
Step-by-step explanation:
In the first layer, there are 6 squares. The second layer has 12 squares.
So, the second term is 6 more than the first term i.e., in general, the number of squares in a layer is 6 greater than the number of squares in its previous layer,
If we generalize this A.P. as arithmetic explicit formula then it becomes
[tex]a_{1} = 6, a_{n} = 6 + a_{n - 1}, n > 0[/tex] (Answer)
Answer:
f(1) = 6; f(n) = 6 + d(n − 1), n > 0
Step-by-step explanation: